PENINGKATAN PRODUKTIVITAS KAMBING KACANG DI KELURAHAN PENATIH DENPASAR TIMUR MELALUI DEMOPLOT PEMBERIAN KONSENTRAT YANG DISUPLEMENTASI AMONIUM SULFAT VS MINERAL MIX - S. PUTRA; I. A. M. SUKARINI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2006)
ABSTRACT In line with the regional government programs in sustaining the agricultural ? livestock farming system. An informative talk on enhancing performances and productivity of kacang goat was held at Penatih, Badung reegency on the 20th Dec. 2002. The aim of the community service is to fulfill the farmer?s knowledge and their technical skill in choosing and applying proportional feed stuff, especially using ammonium sulfate mineral as feed supplement on grass-legume based diet. This material which has the capasity to promote rumen microbial growth and their activity in digesting low quality diets. Composing and mixing concentrate diets has also been demonstrated and 4 dietary treatments were tested using 12 goats during a period of 15 days. Ration ( R) A contained 97% rice bran + 3% am. Sulfate; RB was 97% rice brand + 3% mineral miz; RC was pollard + 3% am. Sulfate and RD was 97% pollard + 3% mineral mix. Body weight gain were monitored through out the trial period. The result indicated that quality of ration caused improvement of performance and productivity of kacang goats. Body weight gain being increased to 0,067 ? 0,300 kg/head/day for diet A, C, and D, which the highest mean values of 0,217 kg/head/day were obtained for diet D. This situation may due to the present of ammonium sulfate plus zinc (Zn) mineral to the legumes basal diet, which can act as metabolic modulator . In general, most of the participants (90%) have a very good responses and acceptance for the beneficial information given to them.